Exploring genetic variability for waterlogging tolerance related traits in early segregation generation in maize (Zea mays) - KUMAR, SANJAY; RANJAN, RUMESH; GARG, TOSH; SINGH, GAGANDEEP; YOUSUF, NIDA; ROHIT; KUMAR, MAHESH (The Indian Journal of Agricultural Sciences, 2026)
Climate change has increased the frequency of abiotic stresses, such as waterlogging (WL), caused by heavy, unpredictable rainfall in compacted soils that adversely affects the growth and yield of maize (Zea mays L.). To breed WL-tolerant maize hybrid, understanding genetic variability for WL tolerance traits in source germplasm is critical. The experiment was conducted during rainy (kharif) season 2023 at Punjab Agricultural University, Ludhiana, Punjab in F2:3 maize populations derived by crossing WL tolerant and susceptible parent for WL tolerance under pot and field conditions. Physiological, root, and yield-related traits were assessed after WL stress at the V3–5 stage for six days. Experiment I identified root dry weight, shoot dry weight, root surface area, and root diameter as promising traits due to high heritability (h2) and genetic advance, suggesting their utility in breeding WL-tolerant lines. Chlorophyll content before (CCBT-P) and after (CCAT-P) treatment showed low heritability, requiring further studies. In Experiment II, yield-related traits like ear height, plant height, and ear yield exhibited moderate to high heritability, making them suitable for selection. The findings highlight the importance of prioritising high-heritability traits for selection and fixing superior lines through continuous selfing. This approach can aid in developing WL tolerant maize hybrids, enhancing productivity in WL prone regions of northern India and supporting sustainable maize farming amid increasing climate-induced abiotic stresses.